Salutogenic approach paradigm of comprehensive and integrated health care - Creagh Bandera, Idalberto; Pérez Ferreiro, Yanet del Carmen; Creagh Bandera, Fidel (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
The health care approach denoted as salutogénesis was reviewed based on the historical, which conceives actions from integrality - integration precepts that enhance technical quality and enhance perceived quality (warmth) in order to achieve well-being and promote the building of a subject, family and community with a style of coping with the health situation that is paid by a professional with a way of thinking - acting proactively, not reactively, which favorably affects the quality of individual and collective life. In this sense, various current flat and electronic scientific publications have been valued, as well as recognized national and international texts, which supports the novelty of the model that is exposed, its usefulness and competitiveness and the relevance of applying it in the context of the Cuban health system. that has the person versus the community as the center, since such an approach always reorients - revitalizes, the promotion of health and prevents lifestyles that favor successfully facing various risks and conditions the reasonable effectiveness of avoiding a given disease and, of course, generating a qualitative enhancement - quantitative regarding, abort - restore, sequelae of damage to health in a given case, then power, from the state of apparent health, a Danger, Vulnerability and Risks type approach, for which it enhances Strengths and reverses Weaknesses and , turns Threats - Opportunities into its target and confronts them-boldly transforms, so that it enhances the well-being of the person, the family and the community.